(untitled) (American Journal of Education and Technology, 2024)
This study aimed to determine the Licensure Examination for Teachers (LET) profile, the Level of Social Support and Expectancy and their relationships and identify the dimensions that predict LET Success Rating. This quantitative study utilized descriptive-correlational design among LET Passers and Licensed Professional Teachers produced by the University of Mindanao from 2019–2023. 303 LPTs composed of 109 Elementary and 194 Secondary teachers selected via convenience and snowball sampling responded to the virtual survey. The collected data were analyzed using mean, standard deviation, spearman correlations, and multiple regressions. Results revealed that 87% of the LPTs were top-performing and had high social support and expectancy levels during their LET preparation. The correlation between social support and the LET Success Rating is positive but very weak. Likewise, the correlation between expectancy and LET Success Rating is positive but very weak. Moreover, social support predicts the LET Success Rating by 1.9%; expectancy predicts it by 0.4%. Furthermore, support from Friends and/or classmates has moderate and positive correlations and has a strong positive predictive power with LET Success Rating.